Optimización del sistema de explotación para la extracción de materiales áridos y pétreos del área minera “Junior acumulada código 600524”, ubicada en el sector Chinguilamaca, entre la parroquia Malacatos-Valladolid del cantón Loja y parroquia Purunuma del cantón Gonzanamá, provincia de Loja. - Tamayo Jaramillo, Ángel Efrén (2016)
The present research work developed at the “Junior Acumulada” mining area Code 600524, located between Loja and Gonzanamá cantons, and dedicated to the extraction of gravels and petrous, it is aimed at improving processes and activities currently performed by the operating system called “TRINCHERA DE CORTE PERPENDICULAR A LA CORRIENTE”. First, the bibliographic information needed was collected and analyzed, and then the area was characterized through field and office work, obtaining information such as topography, geology, geomorphology, hydrology, weather and vegetation. The description of the processes and activities corresponding to the current operating system was developed through a direct observation and field records, detailing its performance technically and machinery used. Furthermore, the performance and the daily production were determined, as well as the financial value of production, establishing the cost for each cubic meter of extracted and stocked material. To define the operating area where current processes and activities are developed, as well as exploitable terraces and volumetric quantification, it was taken into account border, geological, topographical, and safety criteria, among others. This information allowed to define the optimized operating system called "DIQUES TRANSVERSALES CON FRENTE ÚNICO BAJO LÁMINA DE AGUA”. Defined the optimized operating system, There were described and sketched out the processes and activities, taking into account technical parameters to improve its operation. The performance calculation, production of machinery in mentioned conditions and their financial value, allowed determining the cost for each cubic meter of extracted material in this system. Finally, it was performed an economic assessment of the implementation or adjustments to the different processes and activities, defining the viability of the optimized system.